2006
DOI: 10.1634/theoncologist.11-6-641
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Treatment in Cancer Therapy-Induced Early Menopause

Abstract: Young women with breast cancer often experience early menopause as a result of the therapy for their malignant disease. The sudden occurrence of menopause resulting from chemotherapy, oophorectomy, radiation, or gonadal dysgenesis frequently results in hot flashes that begin at a younger age and may occur at a greater frequency and intensity than hot flashes associated with natural menopause.Hormone therapy relieves symptoms effectively in 80%-90% of women who initiate treatment. This therapy, however, is gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 94 publications
1
33
1
2
Order By: Relevance
“…Placebos have been shown to reduce hot flashes by 20-30% within 4 weeks of treatment, and in 15% of women experiencing symptomatic flashes [37,38]. In contrast, NK3R antagonist administration in this study was associated with an approximately 70% reduction in hot flashes over only 7 days of treatment, and this in all 8 women reporting hot flashes.…”
Section: Discussioncontrasting
confidence: 55%
“…Placebos have been shown to reduce hot flashes by 20-30% within 4 weeks of treatment, and in 15% of women experiencing symptomatic flashes [37,38]. In contrast, NK3R antagonist administration in this study was associated with an approximately 70% reduction in hot flashes over only 7 days of treatment, and this in all 8 women reporting hot flashes.…”
Section: Discussioncontrasting
confidence: 55%
“…Progesterone, clonidin and selective serotonin reuptake inhibitors have been shown to reduce hot flashes but may have significant side-effects and are not widely used in clinical settings [4,20]. Hot flashes are reported to be the most prominent side-effect of Tamoxifen medication [4,21,22]. As survival from breast cancer increases there is a corresponding rise in the number of women living with long term consequences of treatment, including hot flashes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this appears to be a consistent problem in hot flashes research, since other investigators have reported that the placebo effect can be as high as 25% on average, with up to a 75% reduction in hot flashes in 15% of women. 45,46 Our review suggests that black cohosh has limited estrogenic activity. Black cohosh does not appear to possess classical estrogenic activity, as measured by breast and uterine tissue proliferation, but may possibly have nonclassical activities as seen by its effects on bone metabolism.…”
Section: Table 5 (Continued)mentioning
confidence: 99%